2018
DOI: 10.1002/cncr.31768
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy for esophageal cancer: Who, when, and what?

Abstract: The perioperative combination of 5‐fluorouracil, oxaliplatin, and docetaxel is a new standard treatment in patients with esophageal carcinoma. However, chemoradiation results in higher R0 surgical resection rates, pathologic complete response, and negative lymph node status. The identification of molecular subsets may influence the design of future studies and guide drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Indeed, the authors charged that Community Care 'exploits us in its demand that women take on this caring, further endangering our mental health and offering no forms of support that are really responsive to women's needs'. 114 A survey conducted by Islington Community Health Council between October and December 1977 into the needs of families and relatives caring for an elderly person at home confirmed this accusation. 115 The report characterized the 35 houses included in the survey as:…”
Section: The Islington Women and Mental Health Projectmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, the authors charged that Community Care 'exploits us in its demand that women take on this caring, further endangering our mental health and offering no forms of support that are really responsive to women's needs'. 114 A survey conducted by Islington Community Health Council between October and December 1977 into the needs of families and relatives caring for an elderly person at home confirmed this accusation. 115 The report characterized the 35 houses included in the survey as:…”
Section: The Islington Women and Mental Health Projectmentioning
confidence: 98%
“…96 Therefore the founders noted the importance of ensuring health care 'is relevant to different ethnic groups, & to challenge racism in the health service.' 97 As Natalie Thomlinson has argued, white feminists' awareness of and activism around racism took the form of a variety of anti-racist practices which were sometimes clumsy, and that failed to challenge white women's dominance over the movement as a whole. 98 In the Islington project we can see further evidence that members of the women's movement were not inattentive to the significance of race and that the theories developed during the 1970s continued to shape feminist activism into the 1980s, albeit manifested in local projects rather than articulated at national conferences.…”
Section: The Islington Women and Mental Health Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Its incidence and mortality rates rank 7th and 6th among all malignant tumors worldwide according to global cancer statistics in 2018 ( 4 ). In recent years, neoadjuvant therapy ( 5 , 6 ), minimally invasive surgery ( 7 , 8 ) and modern precision radiotherapy ( 9 ) for the treatments of esophageal cancer have improved survival times; however, the overall efficacy is still not high, with a 5-year survival rate of 18% based on cases diagnosed between 2005 and 2011 in North America ( 10 ). Natural products are important resources for anticancer drugs ( 11 , 12 ), such as gypenoside L and matrine.…”
Section: Introductionmentioning
confidence: 99%
“…The results of primary surgery appear to be unsatisfactory in locally advanced diseases due to early local recurrence and metastatic spread, which often lead to a high rate of non-curative resections due to microscopic residual tumors (R1). According to these data, interest has focused on the benefits of neoadjuvant chemotherapy (NAC) with or without radiation therapy (RT) [2] before surgery. The MAGIC trial demonstrated that it may be possible to improve overall survival (OS) with perioperative chemotherapy without increasing surgical morbidity; the multimodal approach has subsequently become the routine treatment for GEJ cancers [3].…”
Section: Introductionmentioning
confidence: 99%